A managerial interfaces perspective for competitive action research. Issue 3 (June 2022) - Simsek, Zeki; Heavey, Ciaran; Fox, Brian Curtis
Abstract: Current theory acknowledges the central role of top managers in shaping the firm's overall pattern of competitive activity. But it gives short shrift to the multifaceted processes by which diverse participants affect the strategic work of analyzing, formulating, and implementing competitive actions. We propose managerial interfaces as a complementary perspective – one where interfaces among top managers, relevant stakeholders, and other strategic contributors both enable and constrain that strategic work. We advance propositions regarding how different properties of managerial interfaces give rise to specific competitive action patterns. We conclude with a range of implications for theory and directions for future research.